USING FUZZY SETS TO CONSTRUCT ROUTES OF MIGRATORY BIRDSTO AVOID ZONES OF ECOLOGICAL DISASTERS - MIKHALEVSKYI, VITALII; SKRYPNYK, TETIANA; BORATYNSKYI, KOSTIANTYN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers an approach to modeling migratory bird migration routes, taking into account areas of environmental disasters, caused in particular by military actions, based on the theory of fuzzy sets. A methodology for constructing optimal flight paths is proposed, which takes into account risk factors associated with environmental pollution, climate change and other adverse conditions. The use of fuzzy logic allows for adaptive assessment of the safety of territories and the formation of alternative trajectories, which contributes to the preservation of bird populations and the minimization of losses during migration. Modern algorithms for routing routes and their application in information systems are analyzed, and the impact of the choice of method on the quality of forecasting and route construction is also assessed. The modeling results are presented, which demonstrate the effectiveness of the considered approach in conditions of real environmental threats. The proposed construction approach makes it possible to determine potential places and periods of bird nesting, and makes it possible to carry out the necessary organizational and restoration measures to preserve the bird population. The hostilities in the South, East and other regions of Ukraine affect key migratory routes of birds, in particular over the Black Sea, the Sea of Azov, in the Polissya zone and steppe reserves. Many traditional resting and nesting places of birds have been destroyed or are unsafe due to military threats. Ukraine is an important transit region for many species of migratory birds. Changes in their routes due to the war may have long-term consequences not only for the ecosystems of Ukraine, but also for the ecological balance in Europe and Asia. The use of methods for constructing routes bypassing areas of ecological disasters makes it possible to assess and predict possible changes in bird behavior. This will allow adapting nature conservation measures, minimizing the negative impact of ecological disasters and can help in developing strategies for preserving biodiversity even in conditions of military operations. The development of a forecasting method will help ornithologists, ecologists and environmental organizations make informed decisions for the conservation of migratory species. It can also be useful for agriculture, urban planning and environmental monitoring.
Keywords: fuzzy sets; bird migration; environmental disasters; flight path; route optimization; adaptive modeling